Evaluation of local language learning in the Limola language revitalization - Budiono, Satwiko; Jaya, Taufan (Journal of Applied Studies in Language, 2024)
Limola is one of Indonesia’s endangered languages, makingit imperative to pass on Limola culture and language to a younger generation. The Limolalanguage revitalization program in Sassa Village, Baebunta District, North Luwu Regency, South Sulawesi Province seeks to preserve the Limola language and culture by teaching the younger generation Limola drama, songs, and poetry. Therefore, this study evaluates the key performance indicators of Limola culture and language learning in the revitalization program to identify the identity of the To Limola society after learning Limola culture and language, and (2) evaluate the implementation of the Limola language community-based revitalization. This study used a descriptive qualitative approach that involved desk study data collection techniques and in-depth interviews with the participants and instructors from the Limola language revitalization program. A sociolinguistic in termsof language and identity research approach was taken to analyzethe data and explore the local content in the language learning materials. The data analysis was also based on the CIPP (Context, Input, Process, and Product) evaluation model and language progress indicators to evaluate the implementation success. The results revealed that the Limola revitalization language learning materials have local content that strongly reflects the identity of the To Limola society. While the Limola language revitalization participants learned both the Limola language and culture, the implementation did not appear to have had a significant impact on increasing the interest of the younger generation in using the Limola language.